Corruption and the Nigerian Youth: Implication for Development - OLUWALEYE, Janet Monisola (Advances in Social Sciences Research Journal, 2017)
Corruption is an anathema to development. Its effects cut across all spheres of life. Despite her natural and human resource endowments, corruption has been a major factor obstructing Nigeria’s sustainable development. Considering the manifestations of corruption among Nigerian students in general, the study examines the impacts of corruption among students of Nigerian tertiary institutions on the country’s sustainable socio-economic and political development. Using both primary and secondary data, the study reveals the diverse manifestations of corruption among the students of Nigerian tertiary institutions. These include but are not limited to examination malpractices, procurement of fake certificates, betting, internet scam etc.ng others which are wrong signals to sustainable development of the country. The study recommends that there is need for re-orientation for hard work, integrity and transparency among the Nigerian students to enhance sustainable development. Task force should be put in place to combat corruption among the Nigerian students.